1995
DOI: 10.1097/00000658-199507000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Experimental Human Mesothelioma Using Adenovirus Transfer of the Herpes Simplex Thymidine Kinase Gene

Abstract: ObjectiveThe authors demonstrate the ability of an adenovirus vector expressing the herpes simplex thymidine kinase (HSVtk) gene to treat human malignant mesothelioma growing within the peritoneal cavity of severe combined immunodeficient (SCID) mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 23 publications
1
45
0
Order By: Relevance
“…17,19,51,52 Briefly, the vectors were constructed from an adenovirus serotype 5 (Ad5) backbone lacking most of the viral sequence from the E 1 A and E 1 B regions and a portion of E 3 region. The suicide gene, herpes simplex type I thymidine kinase (HSVtk), was inserted via homologous recombination techniques into the E 1 region of this recombinant E 1 E 3 -deleted vector.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19,51,52 Briefly, the vectors were constructed from an adenovirus serotype 5 (Ad5) backbone lacking most of the viral sequence from the E 1 A and E 1 B regions and a portion of E 3 region. The suicide gene, herpes simplex type I thymidine kinase (HSVtk), was inserted via homologous recombination techniques into the E 1 region of this recombinant E 1 E 3 -deleted vector.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
“…8,9 Accordingly, adenoviral vectors encoding HSVtk (Ad.HSVtk) in combination with GCV have been used in several pre-clinical and clinical suicide gene studies directed against a variety of cancers including brain tumors, 10 head and neck tumors, 11 melanoma, 12,13 ovarian cancer, [14][15][16] and malignant mesothelioma. [17][18][19][20][21] Many of these animal studies have shown some therapeutic effects; however, one of the major shortcomings of adenoviral gene therapy has been the relatively low efficiency of recombinant gene transfer to target tumor tissues in vivo, thus, significantly limiting treatment efficacy. This occurs despite the presence of a 'bystander effect' where transfection of only a small percentage of malignant tumor cells is sufficient to achieve near complete tumor eradication in some animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 The AFP gene is normally expressed in fetal liver We have demonstrated transfer of a therapeutic gene and is transcriptionally silent in adult tissues, but it construct leading to successful in vitro drug sensitizacan be abnormally reactivated in HCC. We favor the tion of human hepatoma cell lines using a recombinant use of promoters specific for malignant cells, because replication-deficient adenovirus vector in a cell typehigh expression of the suicide gene ''HSVtk'' in maligspecific manner, and found a bystander effect of the nant, transformed cells only in a tissue-specific manAdAFPtk-infected cells in vitro.…”
Section: Afp Production By Hcc Cell Linesmentioning
confidence: 99%
“…acceptable, as nontoxic peak levels of GCV in serum among the patients receiving GCV therapy for viral infections reach 15 to 18 mmol/L. 41,44 …”
Section: Afp Production By Hcc Cell Linesmentioning
confidence: 99%
“…1,2 Other investigators have also delivered therapeutic genes into anatomical cavities in which cancer had developed. [3][4][5][6] .…”
mentioning
confidence: 99%